People's library movement - Nair, R Raman (New Delhi Concept, 2000)
This book is a comprehensive evaluation of the People's library movements on how to encourage the common people to become active and participants in development. Scholors from history, sociology, education and Library and Information Science fields also w
Keywords: Libraries-India; Library legislation-India